PRECONS: Reforestation and soil conservation in the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
PRECONS (Programme regional de reboisement et de conservation des sols au Sahel - The Regional Programme for Reforestation and Soil Conservation in the Sahel) is responsible for strengthening regional cooperation within the Sahel for soil and water...